Religion and Nationalism in Chinese Societies - Kuo, Cheng-tian, 1957-; Project Muse. (Amsterdam : Amsterdam University Press, 2017)
This book explores the interaction between religion and nationalism in the Chinese societies of mainland China, Taiwan, and Hong Kong. Cheng-tian Kuo analyses the dominant religions, including Chinese Buddhism, Tibetan Buddhism, Daoism, Christianity, Islam, and folk religions, but he also goes beyond that, showing how in recent decades the Chinese state has tightened its control over religion to an unprecedented degree. Indeed, it could almost be said to have constructed a wholly new religion, Chinese Patriotism. The same period, however, has seen the growth of democratic civil religions, which could challenge the state.
Introduction: Religion, state, and religious nationalism in Chinese societies / Cheng-tian Kuo -- Part I. Chinese religion and nationalism before 1949. 2. The idea of Chineseness and ethnic thought of Wang Fuzhi / Chi-shen Chang -- 3. Missionizing, civilizing, and nationizing: linked concepts of compelled change / Julia C. Schneider -- 4. The nation in religion and religion in the nation / Adam Yuet Chau -- 5. History and legitimacy in contemporary China: towards competing nationalisms / Robert D. Weatherley and Qiang Zhang -- 6. Pilgrimage and Hui Muslim identity in the republican era / Yuan-lin Tsai -- Part II. Religion and nationalism in contemporary China. 7. Religion and the nation: Confucian and New Confucian religious nationalism / Bart Dessein -- 8. Yiguandao under the shadow of nationalism: traitors, conspirators, traditionalists, or loyalists? / Ching-chih Lin -- 9. Daoism and nationalism in modern and contemporary China / Shu-wei Hsieh -- 10. Nationalism matters: among mystics and martyrs of Tibet / Antionio Terrone -- 11. 'We are good citizens': tension between Protestants and the state in contemporary China / Yen-zen Tsai -- Part III. Religion and nationalism in Taiwan and Hong Kong. 12. Religion and national identity in Taiwan: state formation and moral sensibilities / Edmund Frettingham and Yih-Jye Hwang -- 13. Multiple religious and national identities: Mazu pilgrimages across the Taiwan Strait after 1987 / Hsun Chang -- 14. Salvation and rights in Hong Kong / Mariske Westensorp.
English.
Description based on print version record.
Keywords: Chine -- Religion -- Histoire; Taiwan; China; China; Chine -- Religion -- Histoire; China -- Religion -- History; Nationalisme -- Chine; Nationalisme -- Aspect religieux; Religion; Nationalismus; Gesellschaft; Religion; Nationalism -- Religious aspects; Nationalism; RELIGION -- Reference; RELIGION -- Essays; RELIGION -- Comparative Religion; RELIGION -- General; Religious groups: social & cultural aspects; Society and social sciences Society and social sciences; Society and culture: general; Social groups; Religious groups: social and cultural aspects; Nationalisme -- Aspect religieux; Nationalisme -- Chine; Nationalism -- Religious aspects; Nationalism -- China; History; Electronic books